Comparative study of the repair of cracked plates with two different composite patches (Fracture and Structural Integrity, 2020)
The purpose of this study is to analyze the behavior of a crack with and without reinforcement by a composite patch of an aluminum plate in mode I using the finite element method. The repair patch is boron / epoxy and Carbon / epoxy, which are used with great success by many researchersFor the distribution of the stresses according to the various loadings, we can conclude that the effect of repair by patch in composite is very distinct, considering the intensities of stresses which decrease for each repair corresponding to the plate not repaired, therefore, the patch in composite dampens the stress field induced at the crack tip and causes a reduction in stresses. The repair with the Bore / epoxy composite patch is more effective than the Carbon/Epoxy patch, this is due to the mechanical properties and the various characteristics specific to boron/Epoxy which gives very significant and very effective results for the repair
Keywords: Crack; Finite element method; Stresses; Composite; Adhesive